High-capacity Mg-RE (Ce, Y)-Sc-Al-Ca-based solid hydrogen storage alloy for fuel cell and preparation method thereof

By adding multiple rare earth elements and metal elements to MgH2 and using melt fast quenching and mechanical ball milling technology to form nanocrystal structure and catalyst distribution, the problem of insufficient thermodynamic stability and kinetic performance of MgH2 is solved, and high capacity and high Efficient hydrogen absorption and discharge performance, suitable for hydrogen storage applications in fuel cells.

CN119177384AActive Publication Date: 2024-12-24ZHONGXIN (WEISHAN) RARE EARTH NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411307419.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-24
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

MgH2 has high thermodynamic stability, complex activation process, high dissociation temperature, and slow hydrogen absorption/draining kinetics, which limits its widespread application in commercial vehicle-mounted fuel cells.

Method used

Mg-RE(Ce,Y)-Sc-Al-Ca-based solid hydrogen storage alloy is used to alloy by adding multi-component rare earth elements Y and Ce and adding metal elements Sc, Al and Ca. The melt fast quenching technology is used to form. Nano-crystalline structure, and NbF5 and V2O5 catalysts are added for mechanical ball milling to reduce alloy particles and introduce crystal defects, improving the thermodynamic and kinetic properties of hydrogen storage.

Benefits of technology

The hydrogen absorption capacity and kinetic performance of Mg-based alloy are significantly improved, and are suitable as a high-capacity hydrogen storage material for fuel cells, with good cycle stability and suitable for large-scale preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177384A_ABST
    Figure CN119177384A_ABST
Patent Text Reader

Abstract

The invention relates to a high-capacity Mg-RE (Ce, Y)-Sc-A < l-Ca >-based solid hydrogen storage alloy for a fuel cell and a preparation method thereof, the hydrogen storage alloy comprises the following components: Mg95-x-yCexYySc0.5 A < 4.5-z > Caz + m wt.% (NbF5 + V2O5), x, y and z in the formula are atomic ratios, 0.5 < = x < = 2, 0.5 < = y < = 2, 0.5 < = z < = 3, m is the percentage of NbF5 + V2O5 in the alloy, 2 < = m < = 8, and the mass ratio of NbF5 to V2O5 is 1: 1. The preparation method comprises the following steps: carrying out induction heating smelting under the protection of inert gas, and injecting molten alloy into a copper casting mold to obtain an alloy ingot; after the cast ingot is put into a quartz tube to be subjected to induction heating melting, under the pressure action of inert gas, liquid alloy continuously falls on the surface of a rotating water-cooling copper roller in a jetting mode, and rapid quenching alloy of a nanocrystalline microstructure is obtained; and the rapidly quenched alloy is subjected to mechanical crushing and sieving, and then is subjected to ball milling together with catalysts NbF5 and V2O5 in a high-purity argon gas environment, so that the ultrafine grain alloy powder is obtained. Through component design, microstructure regulation and control and addition of a multi-element catalyst, the thermal stability of alloy hydride is reduced, and the hydrogen absorption and desorption thermodynamic and dynamic performance of the alloy is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen storage materials, and in particular provides a high-capacity Mg-RE(Ce, Y)-Sc-Al-Ca-based solid hydrogen storage alloy for fuel cells and a preparation method thereof. Background Art

[0002] The low chemical energy per unit volume of hydrogen limits its commercial application as a fuel. Therefore, many solutions have been studied, and the lack of safe and suitable hydrogen storage materials is a key technical bottleneck for the industrial application of hydrogen in automobiles and portable electronics. Hydrogen storage methods should include large volume, large weight capacity, fast adsorption rate at relatively low temperatures, and long cycle life. Common hydrogen storage methods include high-pressure cylinder hydrogen storage, liquid hydrogen storage, and solid hydride hydrogen storage. However, due to the large volume of compressed hydrogen or serious leakage of liquid hydrogen vaporization, the first two hydrogen storage methods have their own problems and are difficult to achieve effective on-board applications. Solid hydrogen storage technology has become a major development direction of on-board hydrogen source systems with its advantages of low cost, good safety, high energy density, and large capacity.

[0003] Among the metal hydrides discovered so far, MgH 2 It is widely considered to be the most promising candidate material for on-board hydrogen storage due to its large hydrogen storage capacity (~7.6wt%), low cost, light weight, non-toxicity, large quantity, and good reversibility. 2 Some disadvantages of hydrides, such as high thermodynamic stability, complex activation process, high dissociation temperature, and slow hydrogen absorption / desorption kinetics, limit their widespread application in commercial vehicles. Summary of the invention

[0004] The main purpose of the present invention is to improve the hydrogen storage performance of Mg-based alloys, and to provide a high-capacity Mg-RE(Ce, Y)-Sc-Al-Ca-based solid hydrogen storage alloy for fuel cells and a preparation method thereof. Multi-element rare earth elements Y and Ce are added to the alloy, and metal elements Sc, Al, and Ca are added for alloying, and a nanocrystalline structure is obtained by melt rapid quenching technology. On this basis, a small amount of NbF 5 and V 2 O 5 The catalyst is mechanically ball-milled to further reduce the alloy particles and introduce a large number of crystal defects, thereby significantly improving the hydrogen storage thermodynamics and kinetics of the Mg-based alloy.

[0005] The first aspect of the present invention provides a high-capacity Mg-RE(Ce, Y)-Sc-Al-Ca-based solid hydrogen storage alloy for fuel cells, which is characterized in that the alloy contains multiple rare earth elements Ce, Y and metal elements Sc, Al and Ca, and is added with multiple catalysts NbF 5 and V2 O 5 , its composition is: Mg 95-x-y Ce x Y y Sc 0.5 Al 4.5-z Ca z +m wt.%(NbF 5 +V 2 O 5 ), where x, y, z are atomic ratios, and 0.5≤x≤2, 0.5≤y≤2, 0.5≤z≤3, and m is NbF 5 +V 2 O 5 The mass percentage of the alloy is 2≤m≤8. NbF 5 and V 2 O 5 The mass ratio of is 1: 1. The preferred atomic ratio x:y:z=1:1:1.5, m=6.

[0006] The second aspect of the present invention provides a method for preparing a high-capacity Mg-RE(Ce, Y)-Sc-Al-Ca-based solid hydrogen storage alloy for a fuel cell, the preparation steps comprising:

[0007] 1. Ingredients: According to the chemical formula Mg 95-x-y Ce x Y y Sc 0.5 Al 4.5-z Ca z The ingredients are prepared, wherein 0.5≤x≤2, 0.5≤y≤2, 0.5≤z≤3, wherein the Mg and Ca in the chemical formula are increased by 8% during the preparation, and the rare earth Ce and Y are increased by 5% during the preparation, and the metal purity of the raw materials is ≥99.5%;

[0008] 2. Preparation of master alloy: The weighed raw materials are heated by conventional methods, such as arc melting, induction heating melting or other heating methods. The heating conditions are: vacuum to 1×10 -2 -5×10 -5 Pa, 0.01-0.1MPa high-purity helium or a helium + argon mixed gas with a volume ratio of about 1:1 is introduced as a protective gas, and the heating temperature is 1450-1550℃ to obtain molten Mg 95-x-y Ce x Y y Sc 0.5 Al 4.5-z Ca z The liquid master alloy is kept warm for 1-5 minutes; the molten alloy is poured into a copper mold to obtain a master alloy ingot.

[0009] 3. Melt quenching: The ingot prepared in step 2 is placed in a quartz tube with a slit at the bottom, and induction heating is used to completely melt the ingot. The liquid alloy is sprayed from the slit at the bottom of the quartz tube onto the surface of a water-cooled copper roller rotating at a linear speed of 5-20 m / s using the pressure of the protective gas helium, forming a quenched alloy thin strip with a thickness of 100-200 μm and a width of 2-30 mm (the width depends on the length of the nozzle slit), and the grain size is between 20-100 nm.

[0010] 4. Mechanical ball milling: Rapidly quench Mg 95-x-y Ce x Y y Sc 0.5 Al 4.5-z Ca z The alloy was mechanically crushed and passed through a 200-mesh sieve. The sieved alloy powder was mixed with a certain amount of catalyst NbF 5 and V 2 O 5 The stainless steel grinding balls are loaded into a stainless steel ball mill, which is then evacuated and filled with high-purity argon gas. The ball mill is milled for 3-6 hours in a planetary high-energy ball mill, with a ball-to-material ratio of 20:1 and a speed of 350 rpm. During the ball milling process, the ball mill is shut down for 0.5 hours for every hour of continuous operation to prevent the ball mill and the abrasive from overheating.

[0011] 5. Structure and performance test: XRD was used to test the phase structure of the cast and ball-milled powders, high-resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM) were used to observe the morphology and microstructure of the ball-milled alloy particles, and selected area electron diffraction (SAED) was used to determine the crystalline state of the alloy. The semi-automatic Sieverts equipment was used to test the hydrogen absorption activation performance, hydrogen storage capacity and hydrogen absorption and desorption kinetics of the alloy powder. The hydrogen absorption temperature was 260°C and the initial hydrogen pressure was 3MPa; the hydrogen desorption temperature was 260°C and the hydrogen desorption was at 1×10 -4 MPa pressure.

[0012] The application of the technical solution of the present invention has the following technical effects:

[0013] In terms of alloy composition design, trace amounts of multi-element rare earth Ce and Y are added, and a small amount of metal Sc, Al and Ca are added for alloying. Mg and Y form Mg 24 Y 5 phase, Ce and Mg form CeMg 3 phase, Sc and Mg form MgSc phase, Al and Ca form Al 4 It can be seen that the addition of rare earth and various metals can form a variety of intermetallic compounds. Some of these intermetallic compounds are hydrogen-absorbing phases, and some cannot absorb hydrogen, but they have a positive effect on the absorption and release of hydrogen in Mg-based alloys. At the same time, rare earth Ce, Y and metal Ca can form CeH with hydrogen.3 , YH 2 and CaH 2 Hydrides, these hydrides have a significant catalytic effect on the absorption and desorption of hydrogen in Mg-based alloys. A special microstructure with nanocrystalline + trace amorphous is obtained through rapid quenching, which is particularly beneficial to improving the kinetics of hydrogen absorption and desorption in Mg-based alloys. On this basis, the rapid quenching alloy flakes are crushed by mechanical crushing and a small amount of NbF is added. 5 and V 2 O 5 The catalyst is ball-milled for a short time, which improves the surface state of the rapidly quenched alloy while maintaining the microstructure of the rapidly quenched alloy, and brings into play the advantages of the two preparation processes and the combined catalytic effect of the catalyst, so that the thermodynamics and kinetics of hydrogen absorption and desorption of the alloy are further improved. The hydrogen storage alloy powder prepared in this way not only has good hydrogen absorption and desorption capacity and excellent hydrogen absorption and desorption kinetics, but is also very promising to become a hydrogen supply carrier for hydrogen fuel cells. In addition, the preparation process of the alloy is simple and easy to operate, and is very suitable for large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0015] Figure 1a , Figure 1b TEM morphology of the rapidly quenched alloy ribbon and microstructure of Example 1, wherein Figure 1b The ruler in the lower right corner is marked as 5 nm;

[0016] Figure 2 XRD diffraction spectra of the cast alloys of Examples 1-6;

[0017] Figure 3 The SEM morphology of the ball-milled powders of Examples 1-6;

[0018] Figure 4 XRD diffraction spectra of the ball-milled alloys of Examples 1-6;

[0019] Figure 5 HRTEM morphology of the ball-milled powders of Examples 1-6. DETAILED DESCRIPTION

[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0021] The present invention further illustrates the composition and preparation method of the Mg-based hydrogen storage alloy involved in the present invention through the following examples.

[0022] The high-capacity Mg-RE (Ce, Y) -Sc-Al-Ca-based solid hydrogen storage alloy for fuel cells of the present invention has a chemical formula of: Mg 95-x-y Ce x Y y Sc 0.5 Al 4.5-z Ca z +m wt.%(NbF 5 +V 2 O 5 ), where x, y, z are atomic ratios, and 0.5≤x≤2, 0.5≤y≤2, 0.5≤z≤3, and m is NbF 5 +V 2 O 5 The percentage of alloy, 2≤m≤8. AlF 3 and La 2 O 3 The mass ratio of is 1: 1. The preferred atomic ratio x:y:z=1:1:1.5, m=6.

[0023] The preparation method of the high-capacity Mg-based hydrogen storage alloy of the present invention comprises the following steps:

[0024] A. According to the chemical formula Mg 95-x-y Ce x Y y Sc 0.5 Al 4.5-z Ca z Proceed with batching. Since metal Mg and Ca and rare earth Ce and Y have low melting points and are easy to volatilize, 8% more Mg and Ca and 5% more rare earth Ce and Y are added in the batching to compensate for the burn loss;

[0025] B. Place the prepared raw materials in the magnesium oxide crucible in order, with the block rare earth Ce and Y at the bottom of the crucible, the electrolytic Al on top of the rare earth Ce and Y, the block metal Sc and Ca plates on top of the electrolytic Al, and the block Mg on top. After the materials are placed in order, cover the furnace and evacuate to 1×10 -2 -5×10 -5 Pa, filled with high-purity helium at a pressure of 0.01-0.1MPa as protective gas, heated to 1450-1550℃, and obtained molten Mg 95-x-y Ce x Y y Sc 0.5 Al 4.5- z Ca z The liquid master alloy is kept warm in a molten state for 3-5 minutes, and then poured into a copper casting mold to obtain a master alloy ingot.

[0026] C. The ingot prepared in the above step B is placed in a quartz tube with a slit at the bottom, and is heated by medium frequency induction until the ingot is completely melted. The pressure of the protective gas helium is used to spray the liquid alloy from the bottom slit onto the surface of a water-cooled copper roller rotating at a linear speed of 5-20 m / s to obtain a quick-quenched alloy sheet with a thickness of about 100-200 μm.

[0027] D. Rapidly quench Mg 95-x-y Ce x Y y Sc 0.5 Al 4.5-z Ca z After the alloy ribbon was mechanically crushed and passed through a 200-mesh sieve, it was mixed with a certain amount of catalyst NbF 5 +V 2 O 5 and stainless steel grinding balls are mixed and loaded into a stainless steel ball mill, which is then evacuated and filled with high-purity argon gas, and ball milled in an all-round planetary high-energy ball mill for 3-6 hours, preferably 5 hours; the ball-to-material ratio is 20:1; the speed is 350 rpm. During the ball milling process, the ball mill is shut down for 0.5 hours for every 1 hour of continuous operation to prevent the ball mill and the abrasive from overheating. The Mg-RE(Ce,Y)-Sc-Al-Ca-based hydrogen storage material described in this patent is obtained through the above preparation process.

[0028] E. XRD was used to test the structure of the ball-milled powder. High-resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM) were used to observe the morphology and microstructure of the alloy particles before and after hydrogen absorption. Selected area electron diffraction (SAED) was used to determine the crystalline state of the alloy. The gaseous hydrogen storage capacity and hydrogen absorption and desorption kinetics of the alloy powder were tested using a fully automatic Sieverts device. The hydrogen absorption temperature was 260°C, the initial hydrogen pressure of hydrogen absorption was 3 MPa, and the desorption temperature was 260°C and 1×10 -4 MPa pressure.

[0029] The chemical composition and proportion of the specific embodiment of the present invention are selected as follows:

[0030] Example 1: Mg 93 Ce 1 Y 1 Sc 0.5 Al 3 Ca 1.5 +6wt.%(NbF 5 +V 2 O 5 )

[0031] Example 2: Mg 94 Ce 0.5 Y 0.5 Sc 0.5 Al2.5 Ca 2 +5wt.%(NbF 5 +V 2 O 5 )

[0032] Example 3: Mg 92 Ce 1.5 Y 1.5 Sc 0.5 Al 2 Ca 2.5 +4wt.%(NbF 5 +V 2 O 5 )

[0033] Example 4: Mg 91 Ce 2 Y 2 Sc 0.5 Al 3.5 Ca 1 +3wt.%(NbF 5 +V 2 O 5 )

[0034] Example 5: Mg 93 Ce 1 Y 1 Sc 0.5 Al 4 Ca 0.5 +7wt.%(NbF 5 +V 2 O 5 )

[0035] Example 6: Mg 93 Ce 1 Y 1 Sc 0.5 Al 3 Ca 1.5 +8wt.%(NbF 5 +V 2 O 5 )

[0036] Comparative Example 1: Mg 90 Al 10 (Quick quenching + ball milling)

[0037] According to the chemical formula composition of each embodiment, block metal Mg, rare earth metal Ce and Y, electrolytic Al, Sc and Ca are selected. The metal purity requirement is ≥99.5%. The selected block metal is polished to remove the surface oxide layer and weighed according to the chemical dosage ratio. Among them, metal Mg and Ca are increased by 8% during the proportion, and rare earth Ce and Y are increased by 5% to compensate for the burn loss during smelting; during the preparation process, the technical parameters of each stage are as follows: vacuum to 1×10 -2 -5×10 -4 Pa, filled with high-purity helium with a pressure of 0.01-0.1MPa or a helium + argon mixed gas with a volume ratio of 1:1; the melting temperature is 1450-1550℃; vacuum is evacuated to 10 during rapid quenching heating -2 -10 -4 Pa, the surface linear speed of the water-cooled copper roller is 5-20m / s. The quenched flakes are mechanically crushed and passed through a 200-mesh sieve and then mixed with the catalyst NbF 5 +V 2 O 5 and stainless steel grinding balls are mixed and loaded into a stainless steel ball mill, and ball milled for 3-6 hours using an omnidirectional planetary ball mill, and the ball mill is stopped for 0.5 hours for every 1 hour of continuous operation. All process parameters can be appropriately selected within the above range to prepare the hydrogen storage alloy powder described in the patent. Therefore, although the present invention only cites a typical embodiment, this embodiment is applicable to preparation methods with different parameters.

[0038] Process parameters of Example 1: According to the chemical formula Mg 93 Ce 1 Y 1 Sc 0.5 Al 3 Ca 1.5 , select bulk Mg and rare earth Ce and Y, electrolytic Al, Sc and Ca. The purity of these metals is 99.5%. They are weighed according to the chemical dosage ratio, including 920.1 grams of bulk metal Mg, 55.5 grams of metal Ce, 35.2 grams of metal Y, 35.1 grams of electrolytic Al, 8.5 grams of metal Sc, and 24.5 grams of metal Ca. Place the weighed bulk metal in the magnesium oxide crucible of the medium frequency induction furnace according to the designed process, place the bulk rare earth Ce and Y at the bottom of the crucible, place the electrolytic Al on top of the rare earth Ce and Y, place the bulk Sc and Ca plates on top of the electrolytic Al, and place the bulk Mg on the top. Then cover the furnace lid and evacuate for about 30 minutes until the vacuum degree is 5×10 -2Pa, and then fill with high-purity helium protective gas until the pressure reaches -0.04MPa, adjust the power to 5kW, control the temperature at 650℃, melt the metal Mg, and then adjust the power to 25kW, control the temperature at 1550℃, melt the metal Ce and Y. The molten liquid metal is kept warm for 5 minutes to make it uniform, and then the mixed liquid metal is injected into a cylindrical copper mold with a diameter of 30mm and a depth of 80mm, and then cooled for 30 minutes under the helium protective atmosphere and taken out of the furnace to obtain the master alloy ingot.

[0039] Cast Mg 93 Ce 1 Y 1 Sc 0.5 Al 3 Ca 1.5 About 100 grams of alloy rods were placed in a quartz tube with a diameter of 35 mm and a slit of 0.05 mm×20 mm at the bottom; the alloy was heated to melt using a radio frequency of 245 kHz, and the heating power was 15 kW under the protection of a helium atmosphere; the molten alloy was sprayed onto the surface of a water-cooled copper roller at a surface linear velocity of 10 m / s at a helium pressure of 1.05 atm to obtain a thin strip of alloy in a rapid-quenching state with a thickness of about 150 μm and an average grain size of about 52 nm; the rapid-quenching Mg 93 Ce 1 Y 1 Sc 0.5 Al 3 Ca 1.5 The alloy flakes were mechanically crushed and passed through a 200-mesh sieve. 20 g of the sieved alloy powder and catalyst (NbF 5 +V 2 O 5 ) 1.2 g and 400 g of stainless steel grinding balls were mixed and placed in a 250 ml stainless steel ball milling jar, which was evacuated and sealed after being filled with high-purity argon. The jar was ball milled in an all-round planetary high-energy ball mill for 5 hours. The ball mill was stopped for 0.5 hours for every 1 hour of continuous operation.

[0040] Figure 1 shows a rapidly quenched alloy ribbon. The thickness of the test ribbon is about 150 μm. TEM observation shows that the structure of the rapidly quenched alloy ribbon is nanocrystalline + a small amount of amorphous structure, and the average grain size is about 52 nm.

[0041] Figure 2 The XRD patterns of the cast alloys of Examples 1-6 show that after adding rare earth and various metal elements to alloy, various intermetallic compounds are formed. Mg and Y form Mg 24 Y 5 phase, Ce and Mg form CeMg 3 phase, Sc and Mg form MgSc phase, Al and Ca form Al 4Ca phase. It is the appearance of these intermetallic compounds that changes the hydrogen absorption and desorption properties of Mg-based alloys.

[0042] Figure 3 The SEM morphology of the ball-milled powder of Example 1-6 shows that the alloy particles are well dispersed after ball milling and no obvious agglomeration is formed. No free catalyst NbF 5 +V 2 O 5 It can be inferred that it is evenly distributed on the surface of the ball-milled alloy particles. 5 It is very soft and will not cut into the alloy particles during ball milling. 2 O 5 The hardness is very high, and V 2 O 5 The particles are very likely to cut into the interior of the ball-milled alloy particles.

[0043] Figure 4 The XRD spectra of the ball-milled alloys of Examples 1-6 show that the ball-milled materials have nanocrystalline and amorphous structural characteristics.

[0044] Figure 5 The HRTEM morphology of the ball-milled alloys of Examples 1-6 shows that the alloys have nanocrystalline and amorphous structures.

[0045] The solid-state hydrogen absorption and desorption capacity and kinetics of the alloy powder were tested using a fully automatic Sieverts device. The results are shown in Table 1.

[0046] Table 1 Hydrogen absorption and desorption kinetics and cycle stability of alloy powders with different compositions

[0047]

[0048] C max —Saturated hydrogen absorption at an initial hydrogen pressure of 3 MPa and 260°C (wt.%); — Hydrogen absorption within 5 minutes at an initial hydrogen pressure of 3 MPa and 260°C (wt.%), —At an initial pressure of 1×10 -4 MPa and 260°C, the amount of hydrogen released within 20 minutes (wt.%).

[0049] The above results show that the ball-milled alloy powder has high hydrogen absorption and desorption capacity and excellent dynamic performance. In particular, the alloy has good hydrogen desorption performance at a relatively low temperature, and the preparation process is simple and easy to operate, which is very suitable for large-scale preparation of the alloy. Obviously, the hydrogen absorption and desorption capacity of the alloy of the present invention can fully meet the hydrogen capacity requirements of the fuel cell for the hydrogen supply system. Compared with similar alloys at home and abroad, the hydrogen storage performance of the alloy of the present invention has been significantly improved.

[0050] The present invention has found through research that in terms of alloy composition design, element substitution can reduce the thermal stability of Mg-based alloy hydrides and improve their hydrogen absorption and desorption kinetics. In particular, the addition of multi-element rare earth elements Ce and Y can significantly reduce the thermal stability of magnesium hydrides. Since Ce and Y can form highly stable CeH when absorbing hydrogen, 3 and YH 3 These hydrides have a good catalytic effect on the absorption and desorption of hydrogen in Mg-based alloys. At the same time, adding a small amount of Sc, Al and Ca can form a variety of intermetallic compounds, which significantly improves the absorption and desorption kinetics of hydrogen in Mg-based alloys and improves the absorption and desorption thermodynamics of hydrogen in alloys to a certain extent. It is worth noting that some intermetallic compounds can absorb hydrogen themselves, which not only improves the absorption and desorption performance of the alloy, but also ensures that the hydrogen absorption capacity of the alloy will not be significantly reduced.

[0051] In terms of preparation technology, the melt rapid quenching treatment can obtain a structure with ultrafine grains (nanoscale), and the rapid quenching structure contains high-density crystal defects, including dislocations, stacking faults, twins, a large number of grain boundaries, etc. This microstructure is extremely beneficial to improving the thermodynamic and kinetic properties of the alloy. Moreover, unlike ball milling, the ultrafine structure and crystal defects obtained by rapid quenching have higher stability. After multiple cycles of hydrogen absorption and desorption, the grains are not easy to aggregate and grow, which is reflected in the hydrogen absorption and desorption performance. It not only has excellent hydrogen absorption and desorption kinetics, but also has good cycle stability.

[0052] Add two catalysts NbF 5 and V 2 O 5 After a short period of ball milling, the surface state of the alloy is improved while maintaining the microstructure of the rapidly quenched alloy, giving full play to the respective advantages of the two preparation processes. The two catalysts are evenly distributed in the alloy matrix during the ball milling process, and their composite catalytic effect can be fully exerted, thereby improving the thermodynamics and kinetics of hydrogen absorption and desorption of the alloy. NbF 5 The catalytic effect of V is mainly due to its low hardness and good stability. It has a good lubricating effect during the ball milling process, which can effectively prevent the alloy from sticking to the inner wall of the ball mill during the ball milling process, and can ensure the efficiency of the ball milling. 2 O 5 The catalytic effect of the catalyst is that it has a high hardness and has a significant cutting effect on the alloy particles during the ball milling process, making the particles of the ball-milled alloy smaller. After adding two high-stability catalysts and ball milling, they can be evenly distributed between the alloy particles, which will inevitably form a large number of active interfaces between the alloy and the catalyst. This interface provides a good nucleation position for the formation and decomposition of hydrides. It is precisely because of the combination of rapid quenching, ball milling and the addition of catalysts that the thermodynamic and kinetic properties of hydrogen absorption and desorption of the alloy are greatly improved.

[0053] Although the present invention has been described in its preferred embodiments, it is obvious that those skilled in the art may adopt other embodiments, such as changing the component contents and the amount of catalyst added, and may make various deformations and modifications without departing from the design concept of the present invention. These changes are all protected by the present invention.

Claims

1. A high-capacity Mg-RE(Ce,Y)-Sc-Al-Ca-based solid hydrogen storage alloy for fuel cells, the chemical formula of which is: Mg 95-x-y Ce x Y y Sc 0.5 Al 4.5-z Ca z +m wt.%(NbF5+V2O5), where x, y, z are atomic ratios, and 0.5≤x≤2, 0.5≤y≤2, 0.5≤z≤3, m is the mass percentage of NbF5+V2O5 in the alloy, 2≤m≤8. The mass ratio of NbF5 to V2O5 is 1:

1.

2. The hydrogen storage alloy according to claim 1, characterized in that: The preferred atomic ratio of the chemical formula is: x:y:z=1:1:1.5, m=6.

3. A method for preparing a high-capacity Mg-RE(Ce,Y)-Sc-Al-Ca-based solid hydrogen storage alloy for a fuel cell, characterized in that: The following steps are involved: Step 1: According to the chemical formula Mg 95-x-y Ce x Y y Sc 0.5 Al 4.5-z Ca z The ingredients are prepared, wherein x, y, z are atomic ratios, and 0.5≤x≤2, 0.5≤y≤2, 0.5≤z≤3; Step 2: Add the weighed raw materials into the magnesium oxide crucible in order, evacuate the crucible, and then fill it with high-purity helium or helium + argon mixed protective gas, and use induction heating method to obtain molten Mg 95-x-y Ce x Y y Sc 0.5 Al 4.5-z Ca z Liquid alloy, pouring the molten alloy into a copper mold to obtain a cast master alloy ingot; Step 3: placing the master alloy ingot prepared in the above step 2 in a quartz tube with a slit at the bottom, heating the alloy with an induction coil to re-melt the alloy, and using the pressure of the protective gas to spray it out from the slit of the quartz tube, and continuously spray it on the smooth surface of the copper roller to obtain a rapidly quenched alloy thin strip; Step 4: Rapidly quench Mg 95-x-y Ce x Y y Sc 0.5 Al 4.5-z Ca z The alloy is mechanically crushed and sieved, and the sieved alloy powder, NbF5+V2O5 catalyst and stainless steel grinding balls are put into a stainless steel ball mill jar, which is evacuated and filled with high-purity argon gas and then ball-milled in a ball mill.

4. The method for preparing a hydrogen storage alloy according to claim 3, characterized in that: In the step 1, the atomic ratio x:y:z is 1:1:1.

5.

5. The method for preparing a hydrogen storage alloy according to claim 3, characterized in that: In the step 2, the vacuum is pumped to 1×10 -2 to 5×10 -5 Pa, and then filled with 0.01 to 0.1MPa high-purity helium, or helium + argon protective gas with a volume ratio of 1:

1.

6. The method for preparing a hydrogen storage alloy according to claim 3, characterized in that: In the step three, the alloy is continuously sprayed on the smooth surface of a copper roller rotating at a linear speed of 5-20 m / s to obtain a quick-quenched alloy thin strip with a thickness of about 100-200 μm and an average grain size of 20-100 nm.

7. The method for preparing a hydrogen storage alloy according to claim 3, characterized in that: In the step 4, the material is ball-milled in an omnidirectional planetary high-energy ball mill for 3-6 hours, with a ball-to-material ratio of 20:1 and a rotation speed of 350 rpm.

Citation Information

Patent Citations

  • High-capacity RE-Mg-Ni-Co based hydrogen storage alloy and preparation method thereof

    CN103695753A

  • Mg-Ti-RE-Ni-based hydrogen-storage alloy and preparation method thereof

    CN104593651A

  • Nano NdF5 catalyzed RE-Mg-Ti-V-Ni-Al-Co base hydrogen storing alloy and preparing method

    CN106967914A

  • High-capacity hydrogen storing alloy for fuel cell and preparation method of high-capacity hydrogen storing alloy

    CN107338380A

  • LaCl3 catalyzed high-capacity hydrogen storing alloy powder and preparation method thereof

    CN107385300A

Cited By

  • Dysprosium oxide catalyzed multi-component hydrogen storage alloy and preparation method thereof

    CN120210622A

  • A dysprosium oxide catalyzed multi-component hydrogen storage alloy and a preparation method thereof

    CN120210622B